Bequests, taxation and the distribution of wealth in a general equilibrium model - Christian Kleiber; Martin Sexauer; Klaus Wälde (Center for Economic Studies and ifo Institute (CESifo), 2006)
This paper examines the role of bequests and of taxation on bequests for the distribution of wealth. We investigate a model with overlapping generations and heterogenous households where parents derive utility directly from their bequests. Using the coefficient of variation as the measure of inequality, bequests per se diminish the inequality of wealth since they raise private savings and hence average wealth holdings more than the variance of wealth. From a policy perspective, taxing bequests and redistributing government revenue lump-sum among the young generation further decreases wealth inequality.
Keywords: D31; H23; 330; Erbe; Erbschaftsteuer; Vermögensverteilung; Overlapping Generations; Theorie